Osmoprotective activity for Escherichia coli in mammalian renal inner medulla and urine. Correlation of glycine and proline betaines and sorbitol with response to osmotic loads. - S T Chambers; C M Kunin (The Journal of Clinical Investigation, 1987)
Escherichia coli are protected against hypertonic NaCl by human urine. We have shown that this is due in part to the presence of glycine betaine and proline betaine. Several investigators have proposed that betaines and sorbitol are concentrated in the cells of the renal inner medulla where they exert a protective role against urea and extracellular osmotic forces. E. coli was used in the present studies as an "osmosensor" to detect osmoprotective activity in mammalian tissues. The greatest activity was found in extracts of renal inner medulla and to a lesser extent in the renal outer medulla and cortex of several mammalian species. Liver extracts were more active than other nonrenal tissues. Bacterial osmoprotective activity and concentration of glycine betaine in the renal inner medulla of rabbits were found to correlate closely with urinary osmolarity. Concentrations of sorbitol were found to be also increased in the renal inner medulla during osmotic stress, but this compound is not osmoprotective for E. coli. Glycine and proline betaine were recovered in urine of rabbits and were increased in those given high osmotic loads. Only small amounts of proline betaine were recovered in the renal inner medulla. The source from which proline betaine is derived is unknown. Images